A low-cost intervention to promote immediate skin-to-skin contact and improve temperature regulation in Northern Uganda - Nissen, Eva; Svensson, Kristin; Mbalinda, Scovia; Brimdy, Kajsa; Waiswa, Peter; Mpora Odongkara, Beatrice; Hjelmstedt, Anna (African Journal of Midwifery and Women's Health, 2019)
Uninterrupted skin-to-skin contact between mothers and newborns during the first hour after birth has been reported to be 2% in Uganda. Aims To investigate if a low-cost intervention targeting the behaviors of hospital staff would increase skin-to-skin contact and to investigate whether skin-to-skin contact stabilized temperature in the newborn. Methods The study had a quasi-experimental, before and after design. The sample included 110 in the pre-intervention group, and 93 in the post-intervention group. Data collection included observations of skin-to-skin contact and temperature measurements. Data were also collected from medical records and interviews. Findings No infants had skin-to-skin contact before the intervention, whereas the proportion was 54.8% after the intervention. Infants who received skin-to-skin contact (n=51) and infants who did not receive skin-to-skin contact (n=146) increased in temperature; however, infants who received skin-to-skin contact were significantly warmer after 5 minutes and remained so at 60 minutes. Conclusions The intervention increased the practice of skin-to-skin contact, which was found to be safe in regard to temperature stabilization.
Keywords: Low-cost intervention; Newborn temperature; Observation; Skin-to-skin contact